2019
DOI: 10.1021/acs.jafc.9b02180
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Unfolded Protein Response Pathways Involved in the Health-Promoting Effects of Allicin on the Jejunum

Abstract: Intestinal endoplasmic reticulum stress (ERS) triggered by adverse factors disturbs the normal function of the intestine. Allicin has been reported to promote intestinal health and development. In the present study, we established in vivo (35-day-old weaned piglets, 4-week-old mice) and in vitro (IPEC-J2 cell line) ERS models to explore the possible mechanisms by which allicin may benefit intestinal health. This study revealed the following: (1) allicin supplementation improved intestinal morphological indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…19 Recent research has revealed its protective effects on intestinal health because it could reduce cellular ROS, up-regulate the spliced X-box binding protein-1 (XBP-1s) signaling pathway, and alleviate intestinal malfunctions related to the endoplasmic reticulum. 20 Moreover, allicin ameliorated metabolism in hepatic steatosis and high-fat diet mice by regulating the composition of the gut microbiota. 21,22 Owing to the well-reported role of allicin on intestinal protection, we hypothesized that the allicin might have ameliorating effects on AA-induced intestinal barrier and inflammation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 Recent research has revealed its protective effects on intestinal health because it could reduce cellular ROS, up-regulate the spliced X-box binding protein-1 (XBP-1s) signaling pathway, and alleviate intestinal malfunctions related to the endoplasmic reticulum. 20 Moreover, allicin ameliorated metabolism in hepatic steatosis and high-fat diet mice by regulating the composition of the gut microbiota. 21,22 Owing to the well-reported role of allicin on intestinal protection, we hypothesized that the allicin might have ameliorating effects on AA-induced intestinal barrier and inflammation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The procedures for protein extraction and Western blot were described in our previous study (8). In the present study, relative protein levels of p-Nr2 and HO-1 of the IPEC-J2 cell monolayers in each group were determined, using b-actin as an internalreference protein.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 98%
“…Many studies have demonstrated its beneficial roles in anti-microbial, antiinflammatory, anti-oxidative, and anti-cancer activities (6,7). In addition, we previously reported that allicin, as an effective organic osmotic substance, plays an important role in regulating cells' adaptation to endoplasmic reticulum stress (8). Attributed to the activities in inhibiting cell proliferation (9), allicin might be effective in cancer treatment (10).…”
Section: Introductionmentioning
confidence: 99%
“…While apoptosis, inositol-requiring enzyme 1 alpha (IRE-1α), one of the major signaling pathways in UPR, and ER stress signaling protein X-box binding protein 1 (XBP-1) were upregulated by allicin, the second contributing signaling C/EBP homologous protein (CHOP) pathway and cell proliferation could not be affected. As blockage of IRE-1α suppressed the beneficial effects of allicin on tunicamycin-stressed cells such as reduction of ROS and different signaling proteins 78-kDa glucose-regulated protein (GRP78), activating transcription factor 4 (ATF-4), and phosphorylated eukaryotic initiation factor-2 alpha (p-eIF-2α), authors suggest that allicin mainly contributes to intestinal health by activating the IRE-1α signaling pathway [ 93 ].…”
Section: Intestinal Porcine Epithelial Cell Linesmentioning
confidence: 99%